ETIKA DIGITAL DI MEDIA SOSIAL: REVITALISASI HADIS-HADIS HIFZHUL LISAN (MENJAGA LISAN) DALAM MENANGKAL CYBERBULLYING - Rifqi Amrulloh; M. Suparta; Romlah Abu Bakar Askar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation has shifted adolescents' social interaction patterns to cyberspace, unfortunately accompanied by an escalation in cyberbullying and the spread of hoaxes. Among Muslim adolescents, behavioral anomalies have emerged in the form of a separation between ritual piety and social media ethics. This study aims to revitalize the concept of hifzhul lisan (guarding the tongue) from the hadith of the Prophet Muhammad (peace be upon him) as a foundation for contemporary digital ethics (netiquette) to combat cyberbullying. Qualitative methods were used through library research, with thematic hadith analysis (maudhu'i) and content analysis approaches, This study explores the text and contextualization of hadiths narrated by al-Bukhari, Muslim, and at-Tirmidhi. The results show that the activities of typing, creating content, and disseminating information on social media have theological consequences equivalent to conventional oral speech. The contextualization of hadiths gave rise to three main pillars of Islamic netiquette: digital tabayyun (information verification), digital kalam thayyib (positive comment patterns), and digital empathy (transcendental digital piety). This revitalization contributes significantly to deconstructing the effects of online disinhibition and restoring the integration of adolescent morality in cyberspace. Synergy between educational institutions, parents' digital parenting patterns, and adolescent critical awareness is an absolute prerequisite for the successful implementation of this digital ethics formula.